2023
DOI: 10.1186/s12885-023-10639-2
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis and experimental validation of cuproptosis-related lncRNA LINC02154 in clear cell renal cell carcinoma

Abstract: Background Clear cell renal cell carcinoma (ccRCC) is common in urinary system tumors. Cuproptosis is a non-apoptotic cell death pathway. Copper binds to fatty acylated mitochondrial proteins and activates various forms of cell death. LncRNA LINC02154 is significantly highly expressed in cells and tissues of many types of tumors, and the risk signature of LINC02154 in some tumors has been validated for effectiveness. Methods We constructed a risk p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…constructed a five-lncRNA risk model based on cuproptosis- and m6A-related lncRNAs [ 57 ]. In KIRC, LINC02154 is identified to be a cuproptosis-linked gene [ 47 ]. However, here, it was found that NFE4 was a novel cuproptosis- and m6A-related lncRNA.…”
Section: Discussionmentioning
confidence: 99%
“…constructed a five-lncRNA risk model based on cuproptosis- and m6A-related lncRNAs [ 57 ]. In KIRC, LINC02154 is identified to be a cuproptosis-linked gene [ 47 ]. However, here, it was found that NFE4 was a novel cuproptosis- and m6A-related lncRNA.…”
Section: Discussionmentioning
confidence: 99%
“…For example, pazopanib has improved PFS and OS in patients with advanced or recurrent cervical cancer, while AMG.706 (motesanib) inhibits angiogenesis in recurrent ovarian cancer and CEP.701 (lestaurtinib) inhibits the growth of cervical cancer cells [ 60 62 ]. Studies have shown differences in IC50 values of drugs such as pazopanib, sorafenib, sunitinib, and imatinib among different CuRA subgroups of clear cell renal cell carcinoma, bladder cancer, and triple-negative breast cancer [ 63 65 ]. Our study also suggested that in the high CuRA score group, IC50 values of PARP inhibitors ABT.888 (Veliparib), AZD.2281 (Olaparib), and MS.275 (Entinostat) were higher, indicating that these drugs were effective bythe cuproptosis-dependent angiogenesis pathway These studies supported our results of drug sensitivity analysis and suggested that research on anti-cuproptosis-related angiogenesis targeted drugs may bring new treatment ideas and expand the application of drugs in the current dilemma.…”
Section: Discussionmentioning
confidence: 99%
“…ALP and ALBI are widely utilized markers in diverse medical settings. Elevated ALP levels can serve as an indication of bone metastasis in cancer patients, including ccRCC, which is potentially associated with the role of CD276 in cancer progression and metastatic potential [ 40 ]. These findings highlight its potential as a target for cancer immunotherapy [ 41 ].…”
Section: Discussionmentioning
confidence: 99%